Repeat donation and deferral rates in US source plasma donors: Exploratory analysis from the IMPACT trial. Issue 10 (26th July 2021) - Hartmann, Jan; Ragusa, Michael J.; Burchardt, Elmar R.; Manukyan, Zorayr; Popovsky, Mark A.; Leitman, Susan F.
Abstract: Background: The IMPACT trial demonstrated the safety of a new personalized nomogram for plasma donation and provided an opportunity to explore short‐ to mid‐term impact on repeat donation and deferral rates, and factors affecting these. Study Design and Methods: In the IMPACT trial, participants were randomized to donate plasma using an established weight‐based nomogram (control) versus a new personalized nomogram incorporating height, weight, and hematocrit (experimental). In this exploratory analysis, repeat donations (per donor, by study arm) were analyzed using negative binomial generalized linear regression models and descriptive statistics. The mean number of donor deferral events was compared between the two arms using logistic regression and count data modeling approaches and were analyzed by lead cause. Results: The predicted mean number of repeat donations was similar between the control and experimental arms (6.82 vs. 6.62, respectively; p  = .22). Overall, the predicted mean number of repeat donations was significantly higher in males compared with females ( p  < .0001). Naïve donors had on average 2.8/2.7 (control/experimental) fewer repeat donations compared with experienced donors. In 23, 137 donations from 3443 donors, 798 donors (376 control, 422 experimental, p  = .80) had at least one deferral (for any cause). The predicted mean number of deferrals in all categories of interest was not statistically different between the study arms. Conclusion: Similar repeat donation and deferral rates between arms suggest that the new nomogram did not result in disruptions to subsequent donation. Further longitudinal research on mid‐ to long‐term effects is warranted.